Analisis Kinerja dan Studi Pengembangan Curbside serta Parkir Kendaraan di Bandara Sultan Iskandar Muda Aceh Besar - Muhammad Haikal; Yusria Darma; Ruhdi Faisal (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2020)
Sultan Iskandar Muda International Airport currently has an increase in the number of domestic passengers by 8.33% from 2013 - 2017. This passenger growth will have an impact on land-side facilities at airports such as curbside and vehicle parking. This study aims to determine the characteristics of curbside and car parking which are then developed in the existing conditions and future conditions. The method used is using the Federal Aviation Administration AC 150 / 5360-13 (1988), Direktur Jenderal Perhubungan Darat (1996), SNI 03-7046-2004, SKEP // 77 / VI / 2005 and the Forecasting of the ARIMA method. The primary data taken is the curbside facility in the form of data dwell time, vehicle slot distance, and curbside length and width. In the parking lot, the parking duration data is taken at 07.00 - 18.00 WIB. Based on the forecasting of needs in 2027, the number of 2027 passengers is 623 passengers / rush hour, and in 2018, according to SKEP / 77 / VI / 2005 has reached the maximum parking capacity, namely the number of parking lots required by 371 parking lots. So the planning of developing curbside length is 62.72 m, and curbside width 10 m, and building a car park in 2027 with a total parking lot of 586 parking lots at Sultan Iskandar Muda Airport.